Ausbau der Freiflächen-Photovoltaik. Unterstützungs- und Steuerungsmöglichkeiten der Bundesraumordnung und Landesplanung; Expansion of ground-mounted photovoltaic. Support and control options for federal spatial planning and state planning - Hauke von Seht (Raumforschung und Raumordnung / Spatial Research and Planning, 2023)
Photovoltaik-Freiflächenanlagen haben das Potenzial, zu einem der zentralen Elemente des kommenden Energiesystems zu werden. Der Bund sieht inzwischen einen erheblichen und raschen Ausbau vor. Inwieweit in den Regionen und Gemeinden jedoch entsprechende Planungen und Maßnahmen erfolgen, wird absehbar auch von den raumordnerischen Regelungen des Bundes und der Länder abhängen. Im vorliegenden Beitrag wird erläutert, dass hier jeweils erhebliche Unterstützungs- und Steuerungsmöglichkeiten zur Flankierung der Ausbaubemühungen zur Verfügung stehen. Aufgezeigt werden dabei auch Querbezüge zum Erneuerbare-Energien-Gesetz sowie dem Baugesetzbuch und es wird dargelegt, dass die unterschiedlichen Arten von Photovoltaik-Freiflächenanlagen teilweise ein differenziertes Vorgehen erfordern werden. – – Regiopolises and regiopolitan regions are receiving unprecedented attention in German spatial planning policy. In addition to the promotion of the German RegioPole network by the federal government, regiopolises and regiopolitan regions are already designated in several spatial development plans. In the academic discourse, however, regiopolises are hardly taken up. This is particularly evident in the fact that dimensions such as city size (more than 100,000 inhabitants) and spatial location (outside metropolitan regions) are used to empirically identify regiopolises as such. A specific functionality or a specific significance in the German urban system, however, is only hinted at, following the established spatial planning concepts of metropolitan regions and central places. Against this background, this paper examines the question of what constitutes a regional centre or region in terms of its specific functionality and what significance it has in the urban system. The international discourses on second-tires-cities, borrowed size and agglomeration shadow are also taken up.
Keywords: 710; Photovoltaik-Freiflächenanlagen; Raumordnung; erneuerbare Energien; Klimawandel; Stromversorgung; Ground-mounted photovoltaic systems; Spatial planning; Renewable energy; Climate change; Power supply